Promotive Activities through Counseling on Immunization as an Effort to Manage Stunting - Reviani, Nia; Sitompul, Yunita R.M.B; Sanggul, Andriyani Risma; Lumbantobing, Romauli; Tampubolon, Christine Handayani (Asian Journal of Community Services, 2024)
Immunization is an effort to actively create/increase a person's immunity against a disease so that if one day they are exposed to the disease they will not become sick or will only experience mild illness. By providing timely immunization, the community can remain protected and VPD outbreaks can be prevented. Diseases that can be prevented by immunization currently still threaten the world because they can cause death and disability. Based on this, it is very necessary to take preventive and promotive actions related to the importance of immunization. The method used in this activity is through socialization and discussions involving expert speakers in their fields with participants consisting of 67 mothers of toddlers. Participants came from three villages in Jatigede sub-district, Sumedang.